Long-Term Outcome of Sciatic Nerve Regeneration Using Bio3D Conduit Fabricated from Human Fibroblasts in a Rat Sciatic Nerve Model. (8th June 2021) - Ando, Maki; Ikeguchi, Ryosuke; Aoyama, Tomoki; Tanaka, Mai; Noguchi, Takashi; Miyazaki, Yudai; Akieda, Shizuka; Nakayama, Koichi; Matsuda, Shuichi
Previously, we developed a Bio3D conduit fabricated from human fibroblasts and reported a significantly better outcome compared with artificial nerve conduit in the treatment of rat sciatic nerve defect. The purpose of this study is to investigate the long-term safety and nerve regeneration of Bio3D conduit compared with treatments using artificial nerve conduit and autologous nerve transplantation. We used 15 immunodeficient rats and randomly divided them into three groups treated with Bio3D ( n = 5) conduit, silicon tube ( n = 5), and autologous nerve transplantation ( n = 5). We developed Bio3D conduits composed of human fibroblasts and bridged the 5 mm nerve gap created in the rat sciatic nerve. The same procedures were performed to bridge the 5 mm gap with a silicon tube. In the autologous nerve group, we removed the 5 mm sciatic nerve segment and transplanted it. We evaluated the nerve regeneration 24 weeks after surgery. Toe dragging was significantly better in the Bio3D group (0.20 ± 0.28) than in the silicon group (0.6 ± 0.24). The wet muscle weight ratios of the tibial anterior muscle of the Bio3D group (79.85% ± 5.47%) and the autologous nerve group (81.74% ± 2.83%) were significantly higher than that of the silicon group (66.99% ± 3.51%). The number of myelinated axons and mean myelinated axon diameter was significantly higher in the Bio3D group (14708 ± 302 and 5.52 ± 0.44 μm) and the autologous nerve group (14927 ± 5089 and 6.04 ± 0.85 μm) than the silicon group (7429 ± 1465 and 4.36 ± 0.21 μm). No tumors were observed in any of the rats in the Bio3D group at 24 weeks after surgery. The Bio3D group showed significantly better nerve regeneration and there was no significant difference between the Bio3D group and the nerve autograft group in all endpoints.